Analisis Pengaruh Financial Distress dan Reputasi Auditor Terhadap Opini Audit Going Concern pada Sektor Energi di Indonesia - Cahyaning Wulan Pribadi; Made Dudy Satyawan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of financial distress and auditor reputation on the acceptance of going-concern audit opinions in energy sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with an explanatory research design. The data used are secondary data obtained from the company's annual financial statements and independent auditor reports. The research sample was determined using a purposive sampling technique based on certain criteria to obtain companies that meet the research requirements during the observation period. Data analysis was performed using logistic regression with the help of EViews 13 software because the dependent variable is a dichotomous going-concern audit opinion. The results show that financial distress has a negative and significant effect on going-concern audit opinions, while auditor reputation has no significant effect. However, financial distress and auditor reputation simultaneously influence going-concern audit opinions. These findings indicate that a company's financial condition is a more determining factor in issuing going-concern audit opinions than auditor reputation, thus it can be a consideration for management, auditors, and investors in evaluating the company's business continuity.